Model simulation of NO3, N2O5 and ClNO2 at a rural site in Beijing during CAREBeijing-2006 - Wang, H. C.; Lu, K. D.; Tan, Z. F.; K. Sun; X. Li; Hu, M.; Shao, M.; L.M. Zeng; T. Zhu; Zhang, Y. H. (Atmospheric Research, 2017)
A chemical box model was used to study nitrate radical (NO3), dinitrogen pentoxide (N2O5) and nitryl chloride (C1NO(2)) in a rural site during the Campaign of Air Quality Research in Beijing 2006 (CAREBeijing-2006). The model was based on regional atmospheric chemistry mechanism version 2 (RACM(2)) with the heterogeneous uptake of N2O5 and the simplified chloride radical (C1) chemistry mechanism. A high production rate of NO3 with a mean value of 0.8 ppbv/h and low mixing ratios of NO3 and N2O5 (peak values of 17 pptv and 480 pptv, respectively) existed in this site. Budget analysis showed that NO emission suppressed the NO3 chemistry at the surface layer, the reaction of NO3 with VOCs made a similar contribution to NO3 loss as N2O5 heterogeneous uptake. The NO3 chemistry was predominantly controlled by isoprene, and NO3 oxidation produced organic nitrate with a mean value of 0.06 ppbv/h during nighttime. The organic nitrate production initiated by NO3 was equal to that initiated by OH, implying the importance of nighttime chemistry for secondary organic aerosol (SOA) formation. We confirmed that the N2O5 heterogeneous reaction accounted for nighttime particle NO3 enhancement, with a large day to day variability, and made less of a contribution to NOx loss compared to that of OH reacting with NO2. Additionally, abundant C1NO(2), up to 5.0 ppbv, was formed by N2O5 heterogeneous uptake. C1NO(2) was sustained at a high level until noon in spite of the gradually increasing photolysis of C1NO(2) after sunrise. Chlorine activation caused by N2O5 heterogeneous uptake increased primary ROx formation by 5% and accounted for 8% of the net ozone production enhancement in the morning.
Keywords: atmospheric chemistry mechanism; boundary-layer; dinitrogen pentoxide; gas-phase reactions; heterogeneous hydrolysis; nighttime chemistry; nitryl chloride; reactive uptake; southern china; volatile organic-compounds